The Pre-service Teachers' Experiences in Developing Digital Competences in Digital Literacies course - Laura Intan Mercy Febriani Simanjuntak; Effendi Limbong; Ida Wardani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The purpose of this study was to explore pre-service teachers’ experiences in developing digital competences in Digital Literacies course. The study used DigComp 2.0 framework by Vuorikari et al. (2016). The design of the study was qualitative case study. The data sources were focus group interviews and observations with the participants of pre-service teachers of the English Language Education Department class of 2020 in Mulawarman University. The sample of the study was 29 pre-service teachers from class A and class C. The findings of the study showed that pre-service teachers have acquired knowledge and abilities in digital competence areas such as information and data literacy, communication and collaboration, digital content creation, safety, and problem-solving. However, pre-service teachers did not progress in ‘’Copyright and licenses’’ & ‘’Programming’’ sub-competences. Thus, the study suggested future studies to give further instruction for every sub-competence in each competence area and to use DigCompEdu framework.